Pengaruh puasa intermiten 5:2 terhadap kadar malondialdehida pada karyawan pria dewasa dengan obesitas - Karima Yudhistina; Erfi Prafiantini; Novi Silvia Hardiany (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Effect of intermittent fasting 5:2 on plasma malondialdehyde levels in adult male employees with obesityBackground: Obesity is a major risk factor for various non-communicable diseases such as type 2 diabetes mellitus and cardiovascular disease. In obesity, the free radical product will be produced, such as malondialdehyde (MDA) which plays a role in the pathogenesis of various diseases. Intermittent fasting (IF) is an alternative way to reduce free radical levels in the body therefore it can prevent complications of obesity. However, the effect of IF on MDA level in an obese adult male in Jakarta has not been reported.Objective: The objective of this study was to determine the effect of IF on malondialdehyde levels in adult male employees with obesity in Jakarta.Methods: This study used a randomized controlled clinical trial. The subjects were men aged 19-59 years with a body mass index (BMI) ≥ 25 kg/m2, divided into fasting and control groups, each group consists of 25 subjects. Intermittent fasting 5:2 is calorie restriction up to 20-25% was done every Monday and Thursday, and not allowed to eat and drink during 14 hours of fasting. Before the intervention, both groups were given education about balanced nutrition. Association of intermittent fasting with MDA and catalase was analyzed by means of difference formula with a significance limit of 5%.Results: MDA levels post-intervention significantly decreased compared to the pre-intervention both in the fasting group [1,3(0,9-2) nmol/mL to 0,4(0,3-0,6) nmol/mL] and in the control groups [1,4(0,9-1,9) nmol/mL to 0,5(0,3-0,7) nmol/mL]. MDA level post-intervention in the fasting group was significantly lower (p<0,05) compared to the control group.Conclusions: Intermittent fasting 5:2 during 8 weeks can decrease MDA levels in adult males with obesity in Jakarta.